1996
DOI: 10.1557/proc-449-683
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Luminescence in Wurtzite GaN

Abstract: The 364 nm PL-system in GaN is attributed to the formation of dislocation excitons and charged dislocation excitons on c-axis screw dislocations. The binding energy for the dislocation exciton, charged dislocation exciton and a hole on the screw dislocation were determined as 35 meV, 7 meV and 65 meV respectively, in accord with experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…12,16 Sometimes a doublet structure of this peak was observed. 15,18,20 The relative intensity of this peak increased after annealing, especially in water vapor atmosphere. 36 It was noted in Ref.…”
Section: The 342 Ev Peak "Y 2 …mentioning
confidence: 96%
See 2 more Smart Citations
“…12,16 Sometimes a doublet structure of this peak was observed. 15,18,20 The relative intensity of this peak increased after annealing, especially in water vapor atmosphere. 36 It was noted in Ref.…”
Section: The 342 Ev Peak "Y 2 …mentioning
confidence: 96%
“…14,18,21 Others attributed the 3.42 eV peak to a transition from a donor to the valence band where the donor was assumed to be oxygen. 12,13 Some investigators suggested that the 3.42 eV peak is related to structural defects, 10,[15][16][17][18][19][20] in particular to cubic inclusions or stacking faults in the wurtzite GaN 10,18,19 or to c-axis screw dislocations. 20 The 3.42 eV peak, denoted in this study as Y 2 , appeared in many of our as-grown GaN samples with Ga and sometimes N polarity.…”
Section: The 342 Ev Peak "Y 2 …mentioning
confidence: 99%
See 1 more Smart Citation
“…For grown in dislocations, luminescence lines were reported at 3.21 [11] and 3.4 eV [6]. For arrays of dislocations introduced by plastic deformation at ele vated temperatures, emission lines at 1.8, 1.9, 2.4 [12], and 2.9 eV [13] were detected.…”
Section: Introductionmentioning
confidence: 98%
“…Experimental data on the effect of dislocations on GaN luminescence, obtained until recently revealed both the nonradiative nature of recombination at dis locations and the appearance of new spectral lumines cence bands [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%